The type theory and the beginnings of valence - Perkins, Elenore (My University, 1900)
Introduction: Between the years 1820 and 1830, cases of isomerism multiplied so rapidly as to demand explanation. Berzelius said, “The isomerism of compounds in itself presupposes that the position of the atoms in them must be different.” Later, attempts were made to group various organic compounds together upon the hypothetical basis of definite common radicals. The outgrowth of these attempts was the “Older Radical Theory” of Liebig and Berzelius. The chief incentive to such labors was the research of Gay Lussac on cyanogen. He proved that cyanogen existed, unchanged, in various compounds, as well as in the free state. Gay Lussac alo held the view that ethylene was a common constituent of both alcohol and ether. Dumas and Boullay attempted to generalize this idea, to extend it to the derivatives of these substances. They assumed the existence of a radical, aetherin, C2H4 ( H = 1, C = 6, O = 16) in what we now call ethyl compounds. This “aetherin” was analogous to ammonia, being regarded as a base, capable of forming a hydrate with water, and “ethers” (or ethereal salts) with acids.
Citation: Perkins, Elenore. The type theory and the beginnings of valence. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Chemistry; Type Theory; Valence; Theses